Pengaruh Social Media Marketing dan Kualitas Produk terhadap Keputusan Pembelian Melalui Minat Beli di Mattea Social Space - Maylannda Ayu Putri; Rivera Pantro Sukma (Eduturisma, 2023)
The purpose of this study was to determine the effect of Social Media Marketing and product quality on purchasing decisions through buying interest in Mattea Social Space. The data analysis method in this study used the SEM (Structural Equation Model) using SmartPLS 3 software. It used the accidental sampling method for a sample of 200 respondents. The results of the study show that for the direct effect that there is a positive and significant influence of social media marketing on purchasing decisions, there are significant results of social media marketing on purchase intention, product quality has a significant effect on purchasing decisions, product quality has a significant effect on purchase intention and purchase intention has a significant effect on purchasing decisions. For the indirect effect of social media marketing, it has a significant effect on purchasing decisions through buying interest, and product quality does has a significant effect on purchasing decisions through buying interest.